Unemployment in Colombia: An Approach (2020)
One of the most pressing issues currently in Colombia is the high unemployment rate. Although, actually, this is not just a problem for the country, because one of the fundamental macroeconomic objectives of any nation is to contain unemployment. While it is true that the level of unemployment must conform to the size and the composition of the economy analyzed, the unemployment rate should not exceed certain levels, because this could undermine political stability.